Effect of Phosphonic Acid (2-Chloroethyl) on Physical and Chemical Characteristics of Trakya Ilkeren and Red Globe Table Grapes (Vitis viniferaL.) - COBAN, HARUN (Asian Journal of Chemistry, 2010)
In this study, the effect of phosphonic acid (2-chloroethyl) on the physical and chemical characteristics of Red globe and Trakya ilkeren table grapes were determined. The experiment was completely randomized block desing with 10 treatment combinations replicated in three blocks. Ethephon (active ingredient of Ethrel®, containing 480 mg L-1 ethephon) of four dosages and a control (0 control, 150, 300, 450, 600 mg L-1) were applied at a spray volume of 1000 (L ha-1) to bunches using a backpack pressure sprayer with hand to ensure thorough wetting and applications times (T1-T4). The application times (T) may be described as follows :T1-beginning of berry colour; T2-20 to 25 % berry colour; T3-40 to 50 % berry colour and T4-80 to 90 % berry colour. It was found that various ethephon application times and dosages generally had statistically no significant effects on physical characteristics (berry weight, berry length, berry width) and sugar fractions (fructose, β-glucose, α-glucose, sorbitol, galactose) in all grape varieties. However, chemical characteristics were observed a decrease titratable acidity and an increase total soluble solids and the amount of color pigments (total anthocyanins). As results of the study, general recommendations are made of 300 (mg L-1) ethephon for Red globe and Trakya ilkeren table grapes, both applied at 20 to 25 % berry colour (T2).